Proceedings of the 59th Annual Meeting of the Association for Computational Linguistics and the 11th International Joint Confer 2021
DOI: 10.18653/v1/2021.acl-long.224
|View full text |Cite
|
Sign up to set email alerts
|

Cascade versus Direct Speech Translation: Do the Differences Still Make a Difference?

Abstract: Five years after the first published proofs of concept, direct approaches to speech translation (ST) are now competing with traditional cascade solutions. In light of this steady progress, can we claim that the performance gap between the two is closed? Starting from this question, we present a systematic comparison between state-of-the-art systems representative of the two paradigms. Focusing on three language directions (English-German/Italian/Spanish), we conduct automatic and manual evaluations, exploiting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 48 publications
3
28
0
Order By: Relevance
“…Although between 30% and 40% of the translations overall were considered of similar quality by a panel of native speakers of the two languages, the translations generated by the cascade models were preferred by a significant margin in all but one case, where the preferences were equally distributed. These results complement other comparative manual evaluations such as [24], though reaching differing conclusions, as in our study and specific evaluation protocol, cascade translations were preferred overall.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Although between 30% and 40% of the translations overall were considered of similar quality by a panel of native speakers of the two languages, the translations generated by the cascade models were preferred by a significant margin in all but one case, where the preferences were equally distributed. These results complement other comparative manual evaluations such as [24], though reaching differing conclusions, as in our study and specific evaluation protocol, cascade translations were preferred overall.…”
Section: Discussionsupporting
confidence: 84%
“…However, results on the 2021 edition of the shared task have again placed cascade ST as the top-performing approach [25]. Alongside these results, Reference [24] presented an in-depth comparative study of the two main approaches, in three translation directions, via both automatic and manual evaluations based on professional post-editing and annotation. They concluded that, for the language pairs and datasets in their study at least, the gap between the two approaches can be considered closed, as subtle differences between the two are not sufficient for human evaluators to establish a preference.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations